2014
DOI: 10.1111/crj.12209
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intravenous immunoglobulin treatment in immunocompromised children with H1N1 influenza: a clinical observation

Abstract: Our study is important while it is the first one that shows the course of primary immunodeficient children with H1N1 infection who were on regular IVIG replacement. A trial of high-dose IVIG may be a useful adjunctive therapy in severe H1N1 influenza, particularly in the immunocompromised patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Unfortunately, knowledge of the therapeutic effect and the mechanism of IVIG against influenza has been limited, although some findings have been reported 710. Evaluation of the therapeutic effect of IVIG against influenza using an animal model has also been reported 11,12.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, knowledge of the therapeutic effect and the mechanism of IVIG against influenza has been limited, although some findings have been reported 710. Evaluation of the therapeutic effect of IVIG against influenza using an animal model has also been reported 11,12.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the Efficacy of immunoglobulin therapy in influenza pneumonia have also been performed: In one study, NK cell activity as a marker of drug efficacy through antibody-dependent cellular cytotoxicity mechanism was used as a criterion that raised the possibility of treatment efficacy [105]. Another retrospective study found that IVIG administration to immunocompromised children with H1N1 had beneficial effects, including reduced mortality and hospitalization in the intensive care unit [106]. Moreover, a reliable role for IVIG in reducing the inflammatory response was found in a review study that examined the Efficacy of several immunomodulatory mechanisms on the severe form of influenza [107].…”
Section: Pentoxifyllinementioning
confidence: 99%